Automated annotation and quantitation of glycans by liquid chromatography/electrospray ionization mass spectrometric analysis using the MultiGlycan‐ESI computational tool. (15th January 2015) - Hu, Yunli; Zhou, Shiyue; Yu, Chuan‐Yih; Tang, Haixu; Mechref, Yehia
<x xml:space="preserve">Abstract</x> RATIONALE Liquid chromatography/mass spectrometry (LC/MS) is currently considered to be a conventional glycomics analysis strategy due to the high sensitivity and ability to handle complex biological samples. Interpretation of LC/MS data is a major bottleneck in high‐throughput glycomics LC/MS‐based analysis. The complexity of LC/MS data associated with biological samples prompts the needs to develop computational tools capable of facilitating automated data annotation and quantitation. METHODS An LC/MS‐based automated data annotation and quantitation software, MultiGlycan‐ESI, was developed and utilized for glycan quantitation. Data generated by the software from LC/MS analysis of permethylated N‐glycans derived from fetuin were initially validated by manual integration to assess the performance of the software. The performance of MultiGlycan‐ESI was then assessed for the quantitation of permethylated fetuin N‐glycans analyzed at different concentrations or spiked with permethylated N‐glycans derived from human blood serum. RESULTS The relative abundance differences between data generated by the software and those generated by manual integration were less than 5%, indicating the reliability of MultiGlycan‐ESI in quantitation of permethylated glycans analyzed by LC/MS. Automated quantitation resulted in a linear relationship for all six N‐glycans derived from 50 ng to 400 ng fetuin with correlation coefficients (R2) greater than 0.93. Spiking of permethylated fetuin N‐glycans at different concentrations in permethylated N‐glycan samples derived from a 0.02 μL of HBS also exhibited linear agreement with R2 values greater than 0.9. CONCLUSIONS With a variety of options, including mass accuracy, merged adducts, and filtering criteria, MultiGlycan‐ESI allows automated annotation and quantitation of LC/ESI‐MS N‐glycan data. The software allows the reliable quantitation of glycan LC/MS data. The software is reliable for automated glycan quantitation, thus facilitating rapid and reliable high‐throughput glycomics studies. Copyright © 2014 John Wiley & Sons, Ltd.